Impact of uncertainties on greenhouse gas mitigation potential of biogas production from agricultural resources - Meyer-Aurich, Andreas; Schattauer, Alexander; Hellebrand, Hans Jürgen; Klauss, Hilde; Plöchl, Matthias; Berg, Werner (Renewable energy, 2012)
The production of biogas as a renewable resource has emerged rapidly in Germany and other countries with the expectation to substantially mitigate anthropogenic greenhouse gases. However, greenhouse gas (GHG) emissions due to the cultivation of energy crops or leakage at biogas plants may counteract the mitigation effect of biogas use. This study analyzes the GHG mitigation potential of using biogas based on cattle slurry and corn ( Zea mays L.) to produce electrical and thermal energy. The impact of the feedstock chosen, the storage facilities, thermal energy use, and land use change were analyzed by evaluating different scenarios. A special focus is provided with an uncertainty analysis, where the impact of uncertainty of 14 parameters on the variability of the mitigation potential was analyzed with Monte-Carlo simulations. The production of biogas from agricultural resources as an energy source for electrical energy may substantially contribute to the mitigation of GHG emissions by offsetting emissions from fossil resources and by reducing emissions from the storage of animal manure. In the scenarios analyzed GHG emissions calculated with default values were between 0.10 and 0.40 kg CO 2-eq/kWh el, which is 22%–75% less than the GHG emissions caused by the present energy mix in Germany. The analysis demonstrates the variability of the mitigation effect due to uncertainties with technical and environmental processes, which are difficult to control. Uncertainties due to fertilizer induced N 2O emissions from the soil had the biggest impact on the mitigation effect of biogas use when the digestate is stored gas-tight. Otherwise, the uncertainty of emissions from the digestate dominates the variability of GHG emissions of the whole process. Moderate effects are caused by the biogas yield from feedstock, methane leakage, the electrical efficiency of the combined heat and power unit (CHP), and nitrate leaching. A minor impact can be expected from fertilizer volatilization and from the power consumption of the biogas plant. ► Biogas production from cattle slurry and corn can contribute to GHG mitigation. ► GHG mitigation is subject to feedstock used and bioengineering processes. ► Corn use results in GHG mitigation less than 50% compared to fossil resource use. ► Land use change effect may substantially reduce the mitigation potential of corn. ► Variation of GHG mitigation is high due to uncertainties with many processes involved.